Polarization Corrosion Test of Austenitic Stainless Steel 316L after High Temperature Gas Nitriding - Suprihanto, Agus (Departemen Teknik Mesin, Fakultas Teknik, Universitas Diponegoro, 2018)
Austenitic stainless steel 316L is ones of popular metallic biomaterial for implant due to the good mechanical properties and corrosion resistance. However at corrosion media, highly stressed and oxygen-depleted environment, it still susceptible to corrosion. Various methods have been developed to enhance the corrosion resistance of stainless steel such as high temperature gas nitriding. High temperature gas nitriding for 316L has been successfully done. This process is conducted at temperature 1050, 1100 and 1200oC for 15 and 30 minutes before quenching in the water. Polarization corrosion test showed that the corrosion resistance was significant improved for treatment at temperature 1050oC and holding time 15 minutes.